Diagnosing lymphoma in a setting with a high burden of infection: a pediatric case of Epstein-Barr virus-associated aggressive B-cell lymphoma with t(8;14) (q23;q32) and extensive necrosis mimicking tuberculosis - Barros,Mário Henrique Magalhães (2015)
The association of lymphoma with necrotic granuloma can pose diagnostic challenges and delay treatment, especially in settings with a high burden of infection. In these settings, the timely use of cytogenetic and molecular methods is most relevant. Here, we report a case of B-cell lymphoma with t (8;14) in a 5-year-old male child. The lymphoma was associated with necrotic granuloma and was initially misdiagnosed as tuberculosis. Polymerase chain reaction was used to detect clonal lymphoproliferation and to rule out Mycobacterium tuberculosis infection. Tumor cells harbored Epstein-Barr virus and expressed CD20, CD10, BCL6, and Ki67 (30%), leading to the diagnosis of B-cell lymphoma with features intermediate between diffuse large B-cell lymphoma and Burkitt lymphoma.